Wild-isolated Neurospora crassa strains that increase fertility of crosses with segmental aneuploids used to establish that a large duplication suppresses RIP in a smaller duplication - Mario Fehmer; Ashwin Bhat; Felicite K Noubissi; Durgadas P Kasbekar (Fungal Genetics Reports, 2001)
Crosses involving strains bearing large segmental duplications are characteristically barren and produce only very few viable ascospores. We report here that the productivity of duplication x euploid crosses can be influenced by the euploid parent. The yield of ascospores was exceptionally low in crosses with the wild-isolated strains Golikro (FGSC# 4830) and Costa Rica (FGSC# 852) and exceptionally high in crosses with Lahore-1 (FGSC #1824), Dagguluru-1 (FGSC #3360), Okeechobee (FGSC # 3968), and Tiassale (FGSC # 4825). The four strains that increased productivity were used in crosses with strains bearing the duplication Dp(IBj5) together with a small (1.3 kb) duplication of the erg-3 gene. This made it possible to obtain sufficient numbers of progeny to establish that presence of Dp(IBj5) suppresses RIP in erg-3.